Case Study Of Pos Malaysia Berhad - Maniam, Santhi (2006)
Based on the SEPT analysis on the environment in which Pos Malaysia operates on reveal that there are many opportunities for future growth with the inevitable globalisation, technological advancement, domestic economic and social development.